2011
DOI: 10.1186/1868-7083-3-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of depression and use of antidepressive medicines during pregnancy on the methylation status of the IGF2 imprinted control regions in the offspring

Abstract: In utero exposures to environmental factors may result in persistent epigenetic modifications affecting normal development and susceptibility to chronic diseases in later life. We explored the relationship between exposure of the growing fetus to maternal depression or antidepressants and DNA methylation at two differentially methylated regions (DMRs) of the imprinted Insulin-like Growth Factor 2 (IGF2) gene. Aberrant DNA methylation at the IGF2 and neighboring H19 DMRs has been associated with deregulated IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 56 publications
5
50
2
Order By: Relevance
“…Previous findings show that prenatal exposure to famine15 predicts lower IGF2 DMR methylation, and that adult offspring of fathers (but not mothers) exposed prenatally to famine had higher BMIs 64. Paternal obesity65 and maternal depression/antidepressant use66 predict lower IGF2 DMR methylation, and lower IGF2 DMR methylation has been linked to lower plasma IGF and lower birth weight67 and greater childhood obesity risk,49 presumably due to rapid early growth, risk of colorectal cancer41 68 and other conditions 15 16 69 70. A speculative explanation which extends the extant literature is that black fathers’ epigenomes may embody an intergenerational legacy of nutritional/metabolic disadvantage, information that may be carried forward through the germline to subsequent generations 71 65.…”
Section: Discussionmentioning
confidence: 93%
“…Previous findings show that prenatal exposure to famine15 predicts lower IGF2 DMR methylation, and that adult offspring of fathers (but not mothers) exposed prenatally to famine had higher BMIs 64. Paternal obesity65 and maternal depression/antidepressant use66 predict lower IGF2 DMR methylation, and lower IGF2 DMR methylation has been linked to lower plasma IGF and lower birth weight67 and greater childhood obesity risk,49 presumably due to rapid early growth, risk of colorectal cancer41 68 and other conditions 15 16 69 70. A speculative explanation which extends the extant literature is that black fathers’ epigenomes may embody an intergenerational legacy of nutritional/metabolic disadvantage, information that may be carried forward through the germline to subsequent generations 71 65.…”
Section: Discussionmentioning
confidence: 93%
“…Although Murphy et al (31) reported that no differences for IGF2/H19 DMR were found across cell type in cord blood, further studies are needed to confirm that DHA exposure induces DNA methylation changes regardless of blood cell subtypes. There is some evidence that DNA methylation may be altered by paternal BMI (41) or maternal use of antidepressive drugs during pregnancy (40). We did not collect any information on paternal BMI or maternal use of drugs during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…24 We chose the nine imprinted marks in this study because these DMRs regulate genes already known to be important to appropriate growth and development, 25, 26 neurological function 27 and to social and maternal nurturing behaviors (from studies in mice) 25 (for review, see Murphy et al 28 ). In addition, our previous studies have shown that these regions exhibit differential malleability in methylation profiles in response to antidepressant use during pregnancy, 29 maternal depression, 30 smoking, 31 folic acid intake 26 and paternal obesity. 32 To our knowledge, no studies have provided mechanistic insights into the association between antibiotic intake during pregnancy and birth weight, although epigenetic mechanisms have been hypothesized.…”
Section: Introductionmentioning
confidence: 97%